Identification and Characterization of the AREB/ABF Gene Family in Three Orchid Species and Functional Analysis of DcaABI5 in Arabidopsis - Xi Xie; Miaoyan Lin; Gengsheng Xiao; Qin Wang; Zhiyong Li (Plants, 2024)
AREB/ABF (ABA response element binding) proteins in plants are essential for stress responses, while our understanding of AREB/ABFs from orchid species, important traditional medicinal and ornamental plants, is limited. Here, twelve AREB/ABF genes were identified within three orchids’ complete genomes and classified into three groups through phylogenetic analysis, which was further supported with a combined analysis of their conserved motifs and gene structures. The cis-element analysis revealed that hormone response elements as well as light and stress response elements were widely rich in the AREB/ABFs. A prediction analysis of the orchid ABRE/ABF-mediated regulatory network was further constructed through cis-regulatory element (CRE) analysis of their promoter regions. And it revealed that several dominant transcriptional factor (TF) gene families were abundant as potential regulators of these orchid AREB/ABFs. Expression profile analysis using public transcriptomic data suggested that most AREB/ABF genes have distinct tissue-specific expression patterns in orchid plants. Additionally, DcaABI5 as a homolog of ABA INSENSITIVE 5 (ABI5) from Arabidopsis was selected for further analysis. The results showed that transgenic Arabidopsis overexpressing DcaABI5 could rescue the ABA-insensitive phenotype in the mutant abi5. Collectively, these findings will provide valuable information on AREB/ABF genes in orchids.